STATISTICAL APPLICATION OF THE CONTINGENT EVALUATION FOR CONSERVATION OF AGRICULTURAL SOILS IN BENIN - KOMBIENOU, Pocoun Damè; DOSSA, Alfred (My University, 2021)
Land degradation is an environmental problem that constitutes a serious threat and endangers food production and rural livelihoods. Thus, where water and wind erosion, reinforced by human activities, can have negative impacts on soils, there are methods to restore or maintain soil fertility in a context of financial constraints. (Dossa, 2016). The contingent evaluation method is the mathematical tool used to model the willingness to pay (CAP: WTP) of farm households to invest financially in soil conservation techniques in the commune of Kérou in the north-west and on the ADJA Plateau in the south-east of Benin. Its formalisation made it possible to calculate the average CAP E (CAP) on a sample by the following formula: E(CAP)=m(α/σ)/(β/σ). Thus, in estimating the average CAP using the probit model, the tobit model (Tobin, 1958) is tested by the two-step method of Heckman (1979) to control for selection bias in the sample of 385 farm households in Kérou and 267 on the ADJA Plateau. The results of the econometric regression give an average CAP of 1,260.92 FCFA/month/hectare for the adoption of SCTs (soil conservation techniques) in Kérou and 1,557 FCFA/month/hectare on the ADJA Plateau.
Keywords: contingent evaluation; agricultural soil conservation; selection; probit